Expanding access to substance use services and mental health care for people with HIV in Alabama, a technology readiness assessment using a mixed methods approach - Ellen F. Eaton; Kaylee Burgan; Greer McCollum; Sera Levy; James Willig; Michael J. Mugavero; Sushanth Reddy; Eric Wallace; Tom Creger; Stefan Baral; Susanne Fogger; Karen Cropsey (BMC, 2022)
Abstract Background Alabama is one of seven priority states for the National Ending the HIV Epidemic Initiative due to a large rural burden of disease. Mental health (MH) and substance use disorders (SUD) represent obstacles to HIV care in rural areas lacking Medicaid expansion and infrastructure. Evidence-informed technologies, such as telehealth, may enhance SUD and MH services but remain understudied in rural regions. Methods We conducted a readiness assessment using a mixed methods approach to explore opportunities for enhanced SUD and MH screening using electronic patient reported outcomes (ePROs) and telehealth at five Ryan White HIV/AIDS Program-funded clinics in AL. Clinic providers and staff from each site (N = 16) completed the Organizational Readiness to Implement Change (ORIC) assessment and interviews regarding existing services and readiness to change. People with HIV from each site (PLH, N = 18) completed surveys on the acceptability and accessibility of technology for healthcare. Results Surveys and interviews revealed that all clinics screen for depression annually by use of the Patient Health Questionnaire-9 (PHQ9). SUD screening is less frequent and unstandardized. Telehealth is available at all sites, with three of the five sites beginning services due to the COVID-19 pandemic; however, telehealth for MH and SUD services is not standardized across sites. Results demonstrate an overall readiness to adopt standardized screenings and expand telehealth services beyond HIV services at clinics. There were several concerns including Wi-Fi access, staff capacity, and patients' technological literacy. A sample of 18 people with HIV (PWH), ages 18 to 65 years, participated in surveys; all demonstrated adequate technology literacy. A majority had accessed telehealth and were not concerned about it being too complicated or limiting communication. There were some concerns around lack of in-person interaction and lack of a physical exam and high-quality care with telehealth. Conclusion This study of PWH and the clinics that serve them reveals opportunities to expand SUD and MH services in rural regions using technology. Areas for improvement include implementing routine SUD screening, expanding telehealth while maintaining opportunities for in-person interaction, and using standardized ePROs that are completed by patients, in order to minimize stigma and bias.